A rehabilitation nursing approach to the care of extracorporeal membrane oxygenation patients: an internship report - Morais, Ana Catarina Carvalho (2023)
Extracorporeal Life Support devices are utilized as an advanced management strategy for cardiorespiratory failure. It is not a treatment but rather a replacement of heart and/or lungs function while the organs are healing. During this period, patients are typically confined to the Intensive Care Unit and are at risk of complications related to critical care stay and limited body movement. Rehabilitation nursing has been shown in the literature to play an essential role in preventing complications and improving the clinical status of critically ill patients. However, the literature is limited regarding the role of rehabilitation nursing in patients implanted with Extracorporeal Life Support devices. The overall objective of this report is to reflect if rehabilitation nursing has the same positive outcomes in patients with Extracorporeal Life Support devices and what interventions are best to provide optimal conditions for their clinical improvement. To achieve the objective of this report, firstly, we conducted a general search on major considerations regarding Extracorporeal Life Support implanted patients. Then, we conducted an integrative review of the literature using two reference databases: EBSCO and PubMed. We applied this knowledge to a practical field and conducted a case study on a Biventricular Assist Device implanted patient, following the Care Guidelines. We finalize this report with a reflection on the specific competencies of the specialist nurse in rehabilitation nursing and how they were developed during the internship. Through this work, we have discovered that rehabilitation nursing has a significant impact on these patient's pathway, including increased muscular strength, reduced duration of mechanical ventilation, and shortened hospital length of stay with almost no adverse events reported. However, since the literature on this subject is scarce, we understand that rehabilitation nursing work is just beginning, and more research should be done and published on these complex patients